2006
DOI: 10.1021/ef050348l
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Calculations of the Energetics and Kinetics of Jet Fuel Autoxidation Reactions

Abstract: Density functional theory calculations of the energetics and kinetics of important reactions for jet fuel oxidation are reported. The B3LYP functional along with 6-31G(d) and larger basis sets are used for calculation of peroxy radical abstraction reactions from hydrocarbons and heteroatomic species, the reaction of sulfides, disulfides, and phosphines with hydroperoxides to produce nonradical products, and the metal catalysis of hydroperoxide decomposition. Reaction enthalpies and activation energies are dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 44 publications
6
46
1
Order By: Relevance
“…Ethylbenzene was found to produce hydroperoxides at lower temperatures than dodecane highlighting that benzylic hydrogens on alkyl aromatics are more reactive than paraffinic hydrogens. Zabarnick's work found that in jet fuels the oxidation pathways are mainly due to alkyl aromatic oxidation and that the normal approximate 80% concentration of paraffins in jet fuel can be considered unreactive with respect to peroxy radical reactions [21,25]. Zabarnick's work highlights the importance of understanding oxidation of potential single component aromatic blending components.…”
Section: Resultsmentioning
confidence: 99%
“…Ethylbenzene was found to produce hydroperoxides at lower temperatures than dodecane highlighting that benzylic hydrogens on alkyl aromatics are more reactive than paraffinic hydrogens. Zabarnick's work found that in jet fuels the oxidation pathways are mainly due to alkyl aromatic oxidation and that the normal approximate 80% concentration of paraffins in jet fuel can be considered unreactive with respect to peroxy radical reactions [21,25]. Zabarnick's work highlights the importance of understanding oxidation of potential single component aromatic blending components.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of these mechanisms however focused on the chemistry of the hydrocarbon components of the fuel. They indicated that aromatic and cyclic hydrocarbons were substantially more reactive than the parainic compounds in the fuels [9]. It is known that free radical autoxidation of hydrocarbons occurs readily at temperatures between 30 and 60°C.…”
Section: Low Temperature Oxidation Of Fuel Componentsmentioning
confidence: 99%
“…A number of workers have applied ab initio and density functional calculations to predict rates and activation energies of oxidation reactions for different species [41][42][43][44][45][46][47].…”
Section: Modeling Of Lubricant Oxidation Stability Propertiesmentioning
confidence: 99%
“…Zabarnick and Phelps [47] employed density functional theory (DFT) to calculate reaction enthalpies and activation energies for abstraction of hydrogen by peroxy radical from hydrocarbons in the autoxidation of jet fuel. They also used DFT to calculate the X-H bond strength, where X is carbon or heteroatom.…”
Section: Modeling Of Lubricant Oxidation Stability Propertiesmentioning
confidence: 99%